Joint scheduling and routing optimization for deterministic hybrid traffic in time-sensitive networks using constraint programming - Akram, Bilal Omar; Noordin, Nor Kamariah; Hashim, Fazirulhisyam; Rasid, Mohd Fadlee A.; Salman, Mustafa Ismael; Abdulghani, Abdulrahman M. (Institute of Electrical and Electronics Engineers, 2023)
Real-time communications characterized by low-latency, deterministic, and reliable behavior are crucial for the advancement of emerging technologies. Consequently, Time-Sensitive Networking (TSN) has been developed to address the distinct demands of sectors such as automation and autonomous vehicles applications. This is currently achieved through various methods that emphasize the scheduling of critical data traffic. However, many of these methods determine routes independently, potentially impacting the schedulability of transmissions. Additionally, there is a noticeable lack of emphasis on the scheduling and routing of low-priority transmissions within TSN. In this paper, we introduce the Optimized Hybrid Deterministic Scheduling and Routing (OHDSR) approach. This method takes into account the priority of communications to jointly optimize the scheduling and routing of Time-Triggered (TT) communications, while also catering to low-priority Best-Effort (BE) communications. Extensive experimental evaluations show the high efficiency of our proposed method. It ensures not only the prompt delivery of TT communications but also the delivery of BE communications within suitable time frames, with a maximum difference of 14.29% from TT communications, meeting their respective deadlines. Moreover, the evaluation demonstrates the high scalability of the proposed approach, providing improved response times compared to the latest work for both routing and scheduling.